THE CRYSTAL-STRUCTURE OF BENZOYL-HISTIDINE MONOHYDRATE - Frohlich, R.; Arni, R. K.; Bozopoulos, A.; Kavounis, C. A. (R Oldenbourg Verlag, 1994)
The crystal structure of benzoyl-histidine monohydrate (BYLH hereafter), C-13H-12N-3O-3. H2O was determined from three dimensional data of 3012 independent reflections measured on a Enraf-Nonius (CAD4) single crystal diffractometer. The compound crystallizes in the orthorhombic space group P2(1)2(1)2(1) with cell dimensions alpha = 7.102(1) angstrom, b = 13.783(3) angstrom, c = 14.160(4) angstrom, V = 1385.92 angstrom-3, F.W. = 277.28, F(000) = 584 Q(calc) = 1.32 g cm-3 and Z = 4.The structure was solved with direct methods. All positional and anisotropic thermal parameters were refined by full-matrix least-squares calculations. The final reliability factor was R = 0.040, while the weighted one was Rw = 0.034. The H atoms found in the difference Fourier map were refined isotropically.The compound consists of a histidine molecule bound to a benzoyl group. There is also a cocrystallized water molecule stabilized through a hydrogen bridge.The 5-membered ring of the histidine has its tautomeric form, after the transfer of the H atom from the N(delta) to the N(epsilon) atom of the ring. There is an sp2 conformation around C6 while the conformation around C3 is that of sp3. The histidine ring forms with the benzene ring a dihedral angle of 109.8(1)-degree.All angle values and bond distances agree very well with the expected values in the literature.
Keywords: Crystal structure